Virtual Reality-Based Learning Performance in Civil Engineering Education - Kuncoro, Tri; Siswahyudi, Dwi; Hammad, Jehad A.H (Graduate School of Universitas Negeri Malang, 2024)
This research aims to create virtual reality (VR) based learning media for build-ing construction courses and assess how effective it is in improving students' understanding. VR can create an immersive and interactive simulated environ-ment that allows students to learn complex concepts visually and practically. This is the reason why VR is the chosen option. The development processes used were needs analysis, design, development, testing, and evaluation. The final product is a VR application that allows students to interact with building models in three dimensions, perform construction simulations, and better un-derstand various aspects of construction. The results show that virtual reality significantly positively affects the learning process. Students who used virtual reality showed significant improvements in concept understanding, practical skills, and desire to learn. They also expressed positive feedback on the ease of use of virtual reality and its benefits for learning. Conclusion: This research shows that virtual reality has an enormous capacity to improve the quality of construction education. It is recommended that virtual reality be further incor-porated into the civil engineering education curriculum because providing a more engaging and effective learning experience can overcome some of the barriers in conventional learning, such as time and facility limitations.